2023
DOI: 10.1038/s41598-023-30987-0
|View full text |Cite
|
Sign up to set email alerts
|

Pattern-based hybrid book recommendation system using semantic relationships

Abstract: In the fields of machine learning and artificial intelligence, recommendation systems (RS) or recommended engines are commonly used. In today's world, recommendation systems based on user preferences assist consumers in making the best decisions without depleting their cognitive resources. They can be applied to a variety of things, including search engines, travel, music, movies, literature, news, gadgets, and dining. A lot of people utilize RS on social media sites like Facebook, Twitter, and LinkedIn, and i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This data contains around 120k reviews from learners on Coursera's MOOC for multiple courses. Each student has an integer rate between [1,5]. The courses are rated based on the learner's sentiments, learning style, preferences, competency, and adaptive difficulty levels, the student may have.…”
Section: Data Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…This data contains around 120k reviews from learners on Coursera's MOOC for multiple courses. Each student has an integer rate between [1,5]. The courses are rated based on the learner's sentiments, learning style, preferences, competency, and adaptive difficulty levels, the student may have.…”
Section: Data Descriptionmentioning
confidence: 99%
“…While existing RSs have employed techniques like content-based filtering, Collaborative Filtering (CF), and hybrid methods 4,5 . Recently, motivated by the quick development of online learning, various recommendation methods have been developed 6,7 .…”
mentioning
confidence: 99%
“…The results showed that the recommended strategy outperforms the current techniques, with significant advancements. Dongjin Hou [19] developed a personalized book recommendation method using DL models and the www.ijacsa.thesai.org features and rules governing user savings at university libraries. The deep auto encoder (DAE) is initially improved by the LSTM in order to enable the framework to retrieve the temporal aspects of the data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They use a sophisticated recommendation system to suggest products to customers based on purchase history, searches, and browsing behavior. The system uses machine learning algorithms to continuously refine its recommendations, making the shopping experience more personalized and increasing sales (Cai et al, 2021;Ermolina & Tiberius, 2021;Poushneh, 2021) (Carvalho et al, 2019;WANG et al, 2020;Wayesa et al, 2023) 4. Spotify: Spotify uses AI to offer highly personalized music recommendations.…”
Section: Case Studies or Real Facts: Provide Real-life Examples Of Co...mentioning
confidence: 99%